High serum copper as a risk factor of all-cause and cause-specific mortality among US adults, NHANES 2011–2014 - Zeng, Xianghui; Zhou, Lanqian; Zeng, Qingfeng; Zhu, Hengqing; Luo, Jianping (Frontiers in Cardiovascular Medicine, 2024)
Background Several studies have shown that serum copper levels are related to coronary heart disease, diabetes, and cancer. However, the association of serum copper levels with all-cause, cause-specific [including cardiovascular disease (CVD) and cancer] mortality remains unclear. Objectives This study aimed to prospectively examine the association of copper exposure with all-cause, CVD, and cancer mortality among US adults. Methods The data for this analysis was obtained from the National Health and Nutrition Examination Survey (NHANES) between 2011 and 2014. Mortality from all-causes, CVD, and cancer mortality was linked to US National Death Index mortality data. Cox regression models were used to estimate the association between serum copper levels and all-cause, CVD, and cancer mortality. Results A total of 2,863 adults were included in the main study. During the mean follow-up time of 81.2 months, 236 deaths were documented, including 68 deaths from cardiovascular disease and 57 deaths from cancer. The weighted mean overall serum copper levels was 117.2 ug/L. After adjusting for all of the covariates, compared with participants with low (1st tertile, <103 μg/L)/medium (2st tertile, 103–124 μg/L) serum copper levels, participants with high serum copper levels (3rd tertile, ≥124 μg/L) had a 1.75-fold (95% CI, 1.05–2.92)/1.78-fold (1.19,2.69) increase in all-cause mortality, a 2.35-fold (95% CI, 1.04–5.31)/3.84-fold (2.09,7.05) increase in CVD mortality and a 0.97-fold (95% CI, 0.28–3.29)/0.86-fold (0.34,2.13) increase in cancer mortality. In addition, there was a linear dose-response association between serum copper concentration with all-cause and CVD mortality (P for nonlinear > 0.05). Conclusions This prospective study found that serum copper concentrations were linearly associated with all-cause and CVD mortality in US adults. High serum copper levels is a risk factor for all-cause and CVD mortality.